Selected pathological conditions affecting endometrial receptivity - Mekiňová, Lenka; Ješeta, Michal; Crha, Igor; Crha, Karel; Vodička, Jan; Hudeček, Robert; Remundová, Kateřina; Matušková, Eva; Pilka, Radovan (Ceska gynekologie, 2022)
OBJECTIVE: A summary of new knowledge on embryo implantation in dependence on quality of the endometrium. METHODS: Literature review from August 2022 of the relevant publications in Web of Science, Scopus and PubMed/Medline databases, focused on “endometrial receptivity”, “polycystic ovary syndrome”, “endometriosis”, “SARS-CoV-2”. RESULTS: The receptive state of the endometrium is a result of physiological remodeling and immune system activity modulated by the microbio-me. This balance can be disturbed by myomas, polyps, sactosalpings, adenomyosis, endometriosis, polycystic ovary syndrome, infections. The effect of SARS-CoV-2 infection is being discussed. For a successful implantation, timing of transfer is crucial. The ultrasound examination is used conventionally. In specific cases, hysteroscopy and endometrium bio-psy are recommended. Histological and immunohistochemical evaluation is performed together with examination of microbio-me or transcriptome. To support the implantation, gestagenes are used, or metformin in the patients with polycystic ovary syndrome. In cases of a repeated implantation failure, the intrauterine infusion of mononuclear cells or platelet rich plasma is used, subcutaneous application of granulocyte colony stimulating growth factor, intravenous application of atosiban or intrauterine application of human chorionic gonadotropin. CONCLUSION: Recent research in the field of transcriptomics, proteomics and reproductive immunology uncovers the process of implantation more deeply and opens a new stage of the assisted reproduction.
Keywords: syndrom polycystických ovarií; polycystic ovaries; Humans; Chorionic Gonadotropin; secretome; Polycystic Ovary Syndrome; endometrium; Female; lidé; proteome; COVID-19; choriogonadotropin; Embryo Implantation; ženské pohlaví; implantation; endometrióza; endometrial receptivity; adenomyosis; implantace embrya; Endometriosis; SARS-CoV-2; receptivity of endometrium; Endometrium